Courier delivery services comparison web application - Lim, Kai Shen (2022)

(untitled)
The proliferation of online shopping has led to the expansion of the courier industry. This is because it is now much simpler and more cost-effective to provide a variety of digital services, such as order tracking and online payment. Users have to enter the same information into the websites of all of the different courier companies in order to find the most affordable price. This information includes the postcodes of the origin and destination, as well as the weight and dimensions of the package. When it comes to selecting a courier service, the decision-making process can become more difficult due to the absence of comparable features for a given weight. In addition, the specific needs of individual courier services direct the development of each company's unique physical form. It is hoped that the development of this system will make it possible for customers to make educated choices regarding the courier services they use based on a variety of factors including pricing, parcel volumetrics, and location information. Users will have access to a variety of features that were not previously available to them thanks to the incorporation of progressive web application technology into this full-stack web application.